PENGARUH PENAMBAHAN BAHAN PANGAN LOKAL TERHADAP SIFAT ORGANOLEPTIK DAN KANDUNGAN SERAT SNACK BAR SEBAGAI ALTERNATIF JAJANAN TINGGI SERAT - Marisa Wahyu Ningsih; Made Darawati; I Gde Narda Widiada (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : Food snacks circulating in the community generally do not have guaranteed security and balanced nutritional content. So that the development of snacks is very important. One food product that is easily developed can be used as a snack or a daily snack that is a snack bar. The development of snack products in the form of snack bars can be made using local food ingredients. This snack bar formulation will then have a high enough fiber content so that it is expected to be an alternative snack food to reduce the incidence of Obesity. Objective : Knowing the effect of adding local food ingredients to the organoleptic properties and fiber content of snack bars as an alternative to high-fiber snacks. Method : This research is a literature study which summarizes some literature that is relevant to the research theme / topic. Literature is obtained through searches conducted on several internet pages. In this study, the type of data used is secondary data. The literature that was reviewed was first selected according to the inclusion and exclusion criteria. Results : Of the 11 journals reviewed 2 of them stated there was an effect of adding local food to the organoleptic nature of snack bars. And of the 11 journals reviewed 4 of them had a snack bar formulation with a relatively high fiber content. So that the recommended snack bar formulation research Pratama (2019 )as an alternative to high-fiber healthy snacks. Conclusion : Of the 11 journals reviewed 2 of them stated there was an effect of adding local food to the organoleptic nature  and fiber content of snack bars.